Dielectric properties of PFN–PZT composites: From relaxor to normal ferroelectric behavior - Apichart Limpichaipanit (2018)
© 2018 Elsevier Ltd and Techna Group S.r.l. Lead iron niobate (PFN) has been reported as a high dielectric ceramic. However, the fabrication of PFN to obtain high purity needs careful preparation and complex techniques. In this study, lead zirconate titanate (PZT) was added to PFN to produce (1-x)PFN–xPZT composites where x = 0, 0.1, 0.2, 0.3, 0.4 and 0.5. The X-ray diffraction (XRD) patterns confirmed that all ceramics had perovskite structure with Pb2FeNbO6as a second phase when x = 0 and 0.1. Pure PFN could be obtained in the form of PFN–PZT composites with PZT when x = 0.2–0.5. Dielectric behavior of PFN showed relaxor ferroelectric behavior as broad dielectric peak could be observed. The temperature at the maximum dielectric constant increased when PZT was added to PFN ceramics. The change of the degree of diffuseness, the variation of Curie-Weiss behavior and the broadness of dielectric peaks confirmed that the dielectric behavior was less relaxor and more normal ferroelectric when the amount of PZT was increased. Electrical conductivity of PFN–PZT composites was also discussed to explain the change of ferroelectric behavior in relation to the activation energy required for charge hopping process.